High-performance carbon nanotube field-effect transistors with electron mobility of 39.4 cm2V−1s−1 using anion–π interaction doping. (25th January 2023) - Yang, Dongseong; Hwang, Kyoungtae; Kim, Yeon-Ju; Kim, Yunseul; Moon, Yina; Han, Nara; Lee, Minwoo; Lee, Seung-Hoon; Kim, Dong-Yu
Abstract: Single-walled carbon nanotube (SWNT) is desirable next generation semiconductor for flexible, transparent and even stretchable with exceptional electrical characteristics. Here, high-performance n-type semiconducting SWNT field-effect transistors (s-SWNT-FETs) are achieved by chemical doping using anion-π interaction between SWNT and anion of tetrabutylammonium fluoride (TBAF) salt. The Fermi level ( E F ) of SWNT shifts to the conduction band edge with increasing dopant concentration. The doped s-SWNT-FETs exhibit significant improvement in electron mobility (39.4 cm 2 V −1 s −1 ) with high current on/off ratio (>10 4 ) compared to those of un-doped device. The doping using anion–π interaction leads to populate electron density of channel and reduces both channel and contact resistance by 99.0% and 99.6%. Excess carriers introduced by the doping compensate traps by shifting the E F toward conduction band edge. The doped device showed improved current stability after 10 h of bias stress test, while the current of undoped FET decreased by 40.4%. Finally, flexible FETs with TBAF doped s-SWNT network are demonstrated on polyethylene naphthalate substrate and show stable operation after 2000 times bending test. Graphical abstract: Image 1